PENGARUH CITRA MEREK, KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN KONSUMEN - Pramita Enggarwati (University of Merdeka Malang, 2017)
The purpose of this study was to investigate the direct effect of brand image and service quality on customer satisfaction and customer loyalty. This study also investigates the indirect effect of brand image and service quality on customer loyalty through customer satisfaction as a mediating variable. Samples in this study amounted to 170 customers who buy products boutique Zoya in Malang. Sampling method is used purposive sampling method. Hypotheses testing in this research is used PATH analysis. The research found that brand image and service quality has a significant influence on customer satisfaction and customer loyalty. Consumer satisfaction has a significant influence on customer loyalty. Consumer satisfaction is also able to mediate indirect influence brand image and service quality on customer loyalty DOI : https://doi.org/10.26905/jbm.v4i1.1711